Wormhole attack mitigation strategies and their impact on wireless sensor network performance: A literature survey. (2nd August 2022) - Shahid, Hafsa; Ashraf, Humaira; Ullah, Ata; Band, Shahab S.; Elnaffar, Said
Summary: Wireless sensor networks (WSNs) consist of hundreds of small sensors that collect and report data. During data sharing, these WSNs become vulnerable to numerous security threats, including the deadly ones. Mitigating this risk is a real challenge, especially in a low‐resource environment such as a WSN. In this work, using a systematic literature review, we surveyed a large body of research (28 studies) that focused on mitigating wormhole security attacks. Through this study, we evaluate the impact of many proposed security schemes and their impact on the WSN's performance. We compare schemes for effectiveness and pinpoint the limitations. We also analyze the various parameters and metrics used in them and highlight the open research challenges in the field. Abstract : A systematic Literature Review is performed for identifying the relevant 28 manuscripts that mitigate the wormhole attack with less effect on WSN performance. A taxonomy is presented to explore the relevant literature in a comprehensive manner. The manuscript analyzes the security schemes for various parameters and metrics to highlight open research challenges.